Festival of flowers (Fulaich): Unique traditional culture and custom of Kinnaura tribes in Himachal Pradesh, North Western Himalaya, India: FULAICH FESTIVAL OF THE KINNAURA TRIBE (Indian Journal of Traditional Knowledge (IJTK), 2024)
Fairs and festivals are important parts of the lives of tribal communities living in the Indian Himalayan Region. For ages, the Kinnaura tribes of Himachal Pradesh have been highly dependent on locally available plant resources for fulfilling their daily livelihood needs and performing various cultural rituals. In Kinnaur district, 'Fulaich’ is one of the most famous festivals celebrated every year during the 10th August-26th October to express respect and love towards high-altitude wild flowers, to pay homage to departed family members and to celebrate a new birth. According to local tradition, during the festival time, from every village 2-14 persons are selected by the villagers to visit alpine and sub-alpine areas and collect wild flowers, mainly Aconitum violaceum, Bistorta affinis, Bergenia stracheyi, Carex nivalis, Delphinium spp., Hymenidium brunonis, Saussurea gossypiphora, Saussurea obvallata, Poa alpina, etc., and offers them to local deities. It is believed that these flowers keep away evil spirits and bring good health, wealth and prosperity. Therefore, the study was conducted to gather information on different religious plants used by different customs and rituals practiced by Kinnaura tribes during the Fulaich celebration. The present study records 47 plants (Angiosperms 41 spp. and Gymnosperms 6 spp.) belonging to 38 genera and 20 families. The occurrence of 25 native shows the high conservation value of the plants. The study helps to understand how Fulaich is playing an important role in the solidarity and cultural identity of the Kinnaura tribes, along with the conservation of plant species. This festival also has great tourism potential, for which it should be declared an International level festival.